Determinants of building customer loyalty in D’impian Inn Hotel Parit Raja / Ameerah Ismon - Ismon, Ameerah (Faculty of Business and Management, 2011)
In future success in business, it relies on delivering a unique and complete holiday experience. The critical success for the hotel industry is building customer loyalty. It brings customer experiences, service quality, customer value and customer satisfactions are major determinants of customer loyalty. Hence the hotel industry like other industries is realizing the significance of customer centered philosophies with the overall goal in terms of customer satisfaction is to stay as close to their customers as possible.